AB0233 Remission according to RAPID3 (routine assessment of patient index data 3) in patients with rheumatoid arthritis: a cross-sectional study from routine care at 3 usa sites. (15th June 2017) - Castrejon, I; Bergman, MJ; Gibson, KA; Yazici, Y; Block, JA; Pincus, T
Abstract : Background: RAPID3 remission criteria provide similar results to DAS28 criteria, although less stringent compared to ACR/EULAR Boolean criteria. RAPID3 remission criteria are more feasible in routine care 1 and have been reported at 25% in patients from France 1 and 21% from Norway 2 . Objectives: We examined the proportion of patients in remission and 3 other severity categories according to RAPID3 at 3 sites at which MDHAQ is completed by all patients in routine care. Methods: All patients seen at each rheumatology site complete an MDHAQ/RAPID3 at all visits in the waiting area as part of their routine care. The MDHAQ includes 0–10 scores for physical function, pain and patient global estimate, compiled into a 0–30 RAPID3, as well as scores for fatigue, RADAI self-report of painful joints, and demographic data. Physicians complete a global assessment (DOCGL) on a 0–10 visual analog scale (VAS). A random visit with complete questionnaire data for each RA patient from each site was included in the analyses. The proportion of patients in 4 RAPID3 categories, high severity (>12/30), moderate severity (6.1–12), low severity (3.1–6), and remission (≤3), was computed. MDHAQ demographic and clinical measures and DOCGL were compared in the 4 RAPID3 severity groups using chi-square and ANOVA tests. Results: 420 RA patients from the 3 sites were analyzed. Remission rates according to RAPID3 severity ranged from 23% to 26%, similar to reported rates from France and Norway. Low severity ranged from 7–24%, moderate severity from 23–29% and high severity from 21–46%. Age and sex were similar in the disease severity categories at the 3 sites (Table). Patients in the moderate and high severity groups at each site had higher scores for fatigue, RADAI self-reported joint pain, and DOCGL. Conclusions: Similar RAPID3 remission rates were seen at 3 USA sites (about 24%), comparable to results from France and Norway. References: Castrejon I, Dougados M, et al. J Rheumatol 2013, 40(4):386–393. Uhlig T, Lie E, et al. J Rheumatol 2016, 43(4):716–723. Disclosure of Interest: I. Castrejon: None declared, M. Bergman: None declared, K. Gibson: None declared, Y. Yazici: None declared, J. Block: None declared, T. Pincus Shareholder of: Health Report Services, Inc